2022
DOI: 10.1007/s00167-022-07139-4
|View full text |Cite
|
Sign up to set email alerts
|

Age and synovitis affect the results of the treatment of knee osteoarthritis with Microfragmented Autologous Fat Tissue

Abstract: Purpose This study aims to assess the effectiveness of Microfragmented Autologous Fat Tissue (MFAT) treatment for knee osteoarthritis and to investigate whether patients’ pre-treatment clinical condition, such as synovitis, correlates with clinical outcomes, to identify potential predicting factors for the success or failure of the treatment. Methods In this prospective Cohort Study Level II multicentric trial, consecutive patients with a diagnosis of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The mean BMI went from 24.7 [ 50 ] to > 35 [ 40 ] for MM-AT and from 26.0 [ 42 ] to 31.0 [ 29 ] for the control groups (12 studies did not report BMI). Patients presented different OA grades, often measured with KL classification: nine studies on KL 1–4 [ 28 , 29 , 39 , 44 , 45 , 46 , 54 , 56 , 59 ], eight studies on KL 3–4 [ 30 , 33 , 35 , 40 , 41 , 47 , 48 , 55 ], three studies on KL 2–3 [ 34 , 42 , 50 ], three studies on KL 1–3 [ 34 , 44 , 51 ], two studies on KL 1–2 [ 32 , 37 ], and two studies on KL 2–4 [ 36 , 53 ]. In addition, patients with mild, moderate, or severe OA grade [ 43 ], ICRS grade of 2–4 [ 51 , 52 ], and American College of Rheumatology criteria 1–3 [ 57 ] were also evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean BMI went from 24.7 [ 50 ] to > 35 [ 40 ] for MM-AT and from 26.0 [ 42 ] to 31.0 [ 29 ] for the control groups (12 studies did not report BMI). Patients presented different OA grades, often measured with KL classification: nine studies on KL 1–4 [ 28 , 29 , 39 , 44 , 45 , 46 , 54 , 56 , 59 ], eight studies on KL 3–4 [ 30 , 33 , 35 , 40 , 41 , 47 , 48 , 55 ], three studies on KL 2–3 [ 34 , 42 , 50 ], three studies on KL 1–3 [ 34 , 44 , 51 ], two studies on KL 1–2 [ 32 , 37 ], and two studies on KL 2–4 [ 36 , 53 ]. In addition, patients with mild, moderate, or severe OA grade [ 43 ], ICRS grade of 2–4 [ 51 , 52 ], and American College of Rheumatology criteria 1–3 [ 57 ] were also evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In the other four studies, Lipocell (Tiss’You, RSM) [ 27 ], Hy-tissue SVF Separation System kit (Fidia, Abano Terme, Italy) [ 50 ], MyStemTM kit (MyStem, Wilmington, DE, USA) [ 53 ], and Tulip Soft Harvest GOLD System (Tulip Medical, San Diego, CA, USA) [ 49 ] were employed, respectively. Only in four studies was the adipose tissue characterized before injection: immunophenotype analysis and viability [ 29 , 34 , 40 ], total nucleated cell count [ 29 ], and histology of lipoaspirate [ 42 ] were evaluated. Some studies did not indicate the amount (ml) of injected MM-AT; when reported, the amount was very variable, from a minimum of 3 mL [ 34 ] to a maximum of 19 mL [ 46 ], with 10 mL being the most commonly injected dose [ 27 , 28 , 30 , 31 , 41 , 44 , 49 , 50 , 51 , 52 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell injections have not proven to be very effective in repairing damaged cartilage, but they have been effective in clinical trials to affect pain and disability [ 99 , 100 ]. However, effectiveness may be negatively influenced by the intra-articular environment, particularly the presence of inflammation [ 4 , 101 ], in spite of their possible immunomodulatory role [ 102 , 103 ]. Some pilot studies with tissue-engineered constructs with autologous synovium-derived mesenchymal stem/stromal cells have indicated the good potential to restore cartilage in cartilage defects prior to the development of overt knee OA [ 104 , 105 ].…”
Section: Implications From Subtyping For Conservative Treatment For K...mentioning
confidence: 99%